Aplikasi Reservasi Parkir Inap Menggunakan Metode Fishbone Diagram dan QR-Code - Yostian Ari Sujarwo; Anita Ratnasari (ISB Atma Luhur, 2020)
Currently parking system that is running in Pt. Sanggraha Daksamitra still uses a conventional parking system. When the driver wants to do parking, driver first presses the analog button on the parking gate to get a parking ticket. Lack of maintenance on the parking gate causes vehicle jams in the parking entrance area. To minimize errors that occur, the fishbone diagram analysis method is used to analyze the problem. After the problem was found, a parking reservation was developed that used qr-code as a scanner identification in the parking system. The system produced in this study is expected to facilitate parking drivers who want to park their vehicles in the parking area of Pt. Sanggraha Daksamitra. The results of this system will be tested using blackbox testing.